Pengaruh Faktor Internal Terhadap Pembelian Impulsif Belanja Online Pada Generasi Z - Nurmasari Nuraini Desty; Latifah Putranti; Fitriani Nur Annisa (Program Studi Manajemen, Fakultas Ekonomi, Universitas Islam Majapahit, Jawa Timur, Indonesia, 2023)
The Covid-19 pandemic has captured the attention of the world community, especially in Indonesia. The impact of Covid-19 has made some people aware of the importance of online shopping. It is been proven that online shopping can have a positive impact on some people. This purpose of this study was to analyze impulse buying tendency, shopping enjoyment tendency, consumer mood, and person situation towards online shopping impulse buying in the generation Z. This research is a type of associative research with a total of 110 respondents. The sampling method used in this study was a survey method using a questionnaire via the google form. Variables of impulse buying tendency and person’s situation have a positive and significant effect, while shopping enjoyment tendency and customer mood have a positive and insignificant effect. This shows that online shopping impulse buying in generation Z are more oriented towards impulse buying tendencies and consumer moods compared to shopping satisfaction tendencies and moods after making purchases in online shopping applications.